2010
DOI: 10.1016/j.jprot.2010.01.014
|View full text |Cite
|
Sign up to set email alerts
|

DIGE analysis of rat skeletal muscle proteins using nonionic detergent phase extraction of young adult versus aged gastrocnemius tissue

Abstract: Contractile weakness and loss of muscle mass are critical features of the aging process in mammalians. Age-related fibre wasting has a profound effect on muscle metabolism, fibre type distribution and the overall physiological integrity of the neuromuscular system. This study has used mass spectrometry-based proteomics to investigate the fate of the aging rat muscle proteome. Using nonionic detergent phase extraction, this report shows that the aged gastrocnemius muscle exhibits a generally perturbed protein e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
33
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 55 publications
8
33
0
Order By: Relevance
“…ATP synthase expression also increased with advancing age in the trophocytes and fat cells of workers. Previous studies have reported similar findings, showing that ATP synthase expression increases with advancing age in the brains and muscle of rats (Nicoletti et al 1995;Chang et al 2007;Doran et al 2008;Donoghue et al 2010), and in muscle of humans (Gelfi et al 2006). Although ND1 and ATP synthase expression measured in absolute terms increased with advancing age in the trophocytes and fat cells of workers, the relative expression of ND1 and ATP synthase normalized to mitochondrial density and VDAC1 was not significantly different.…”
Section: δψMsupporting
confidence: 71%
“…ATP synthase expression also increased with advancing age in the trophocytes and fat cells of workers. Previous studies have reported similar findings, showing that ATP synthase expression increases with advancing age in the brains and muscle of rats (Nicoletti et al 1995;Chang et al 2007;Doran et al 2008;Donoghue et al 2010), and in muscle of humans (Gelfi et al 2006). Although ND1 and ATP synthase expression measured in absolute terms increased with advancing age in the trophocytes and fat cells of workers, the relative expression of ND1 and ATP synthase normalized to mitochondrial density and VDAC1 was not significantly different.…”
Section: δψMsupporting
confidence: 71%
“…As differences exist in fat accumulation between BB-and AA-sired steers, the authors took care during tissue collection to harvest lean muscle tissue only, avoiding intramuscular fat. In addition the protocol used in this study was optimized for protein extraction from muscle tissue (Mullen et al, 2011;Donoghue et al, 2010). There is also no evidence of differential expression of markers of fat metabolism between the AA-and BB-sired steers in the current study.…”
Section: Effect Of Epd Cwt On Protein Abundancementioning
confidence: 83%
“…Progenesis SameSpots analysis (SSA) was used to identify proteins of interest as described by Donoghue et al (2010) and Mullen et al (2011). The gel images were placed into groups (AA, BB, AA-High, and AALow), and analysis was carried as follows: AA vs. BB, AA-High vs. AA-Low, and BB-High vs. BB-Low.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we used this approach to enrich plasma membrane proteins from cultured myoblasts. Cell surface proteins were biotinylated using Sulfo-NHS-LC-Biotin (biotin) and solubilized using RIPA buffer (35,36), and the biotinylated proteins were isolated using streptavidin-conjugated agarose or magnetic beads, as described under "Experimental Procedures." Magnetic beads allowed greater recovery of proteins as compared with agarose beads (data not shown) and were used for all subsequent experiments.…”
Section: Isolation Of Sarcolemmal Proteome Using the Membrane Sol-mentioning
confidence: 99%